Sistem Pengendalian Internal Dana Pihak Ketiga pada Bank Mandiri Taspen KCP Karangnunggal - Awaliyah, Halimatul; Romdoni, Nijar Kurnia (POLITEKNIK LP3I, 2024)
At the beginning of 2022, Bank Mandiri Taspen management will not only focus on lending, but will also start encouraging each Branch Office to expand the volume of Third Party Funds as a contributor to profit growth. The purpose of this research is to determine the Internal Control System for Third Party Funds implemented by Bank Mandiri Taspen Karangnunggal Sub-Branch Office. The research method used is a qualitative method that describes facts and events that occur in the field. The data used by the author in analyzing the Internal Control System for Third Party Funds comes from primary data and secondary data. After analyzing and discussing the problem, the author came to the conclusion that the Internal Control System for Third Party Funds at Bank Mandiri Taspen Karangnunggal Sub-Branch Office has been implemented well.